Evaluation of Project-Based Learning at a Polytechnic in Malaysia: an Input Aspect Evaluation Research - Sadrina Sadrina; Ramlee Mustapha (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2016)
The purpose of the study was to evaluate the effectiveness of Project-Based Learning in the Mechanical Engineering Department at the Polytechnic in Malaysia. This study was designed with Context, Input, Process and Product (CIPP) model. Project-Based Learning is a different approach than the traditional learning in the sense that it is a student-centered learning approach based on the principles of constructivism. However, this present paper focused on the input aspect with comparing students’ and supervisor’ perspective. The input dimension assesses the module and supervisor’s readiness. This study involved a random sample of 118 students and 43 supervisors in the Mechanical Engineering Department in Polytechnic Kota Bharu Malaysia. The instrument used in this study were a set of questionnaire. The study found that both the students and supervisors agreed that Project-Based Learning approach is appropriate for the final project course J5012. In addition, both groups of respondents believed that the supervisors possesed adequate technical knowledge and implemented supervisory duties effectively. Nevertheless, students perceived the module content was hard to understand.